Entrepreneurial Curriculum Development through the Production of Eco Print Batik for Primary School - Ranti Kurniasih; Slamet Santoso; Fery Setiawan; Nur Sayidatul Muntiah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study is designed to cultivate a primary school curriculum that is particularly related to entrepreneurship. It is vital for primary school students to recognize and be taught Entrepreneurial education earlier as a paramount component in enhancing their independence and competence to seize the opportunities in the era of free marketplace today. Not only is this research driven by the fact that the introduction of entrepreneurial-related professions has been low compared to other professions, but also conducted to explore and stimulate the entrepreneurship values of primary school students, empowering the human resources competence. Entrepreneurial-based curriculum can direct the learning process of both students and teachers possessing indispensable roles to cultivate concepts concerning entrepreneurial activities. This curriculum development, ultimately, becomes a challenge to encounter an economic crisis, as well as, an opportunity to prepare young generations that are not limited to be ready to work but open field work.